2016
DOI: 10.1371/journal.pone.0158446
|View full text |Cite
|
Sign up to set email alerts
|

The Electrophysiology of Basic Phrase Building

Abstract: A defining trait of linguistic competence is the ability to combine elements into increasingly complex structures to denote, and to comprehend, a potentially infinite number of meanings. Recent magnetoencephalography (MEG) work has investigated these processes by comparing the response to nouns in combinatorial (blue car) and non-combinatorial (rnsh car) contexts. In the current study we extended this paradigm using electroencephalography (EEG) to dissociate the role of semantic content from phonological well-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 66 publications
7
22
0
Order By: Relevance
“…Either way, our data are consistent with the hypothesis that syntax-driven meaning composition modulates the P600's amplitude (Baggio 2018), and with proposals relating the P600 to operations at the syntax-semantics interface (Bornkessel-Schlesewsky & Schlesewsky, 2008;Kuperberg, 2007). These results do not support the view that phrasal composition is reflected by the N400 (Neufeld et al, 2016), nor are our findings in line with MEG studies indicating that compositional processing occurs at around 400 msec in the vmPFC (e.g. , 2013.…”
Section: Effects Of Phrasal Meaning Composition: P600 Modulationssupporting
confidence: 73%
See 2 more Smart Citations
“…Either way, our data are consistent with the hypothesis that syntax-driven meaning composition modulates the P600's amplitude (Baggio 2018), and with proposals relating the P600 to operations at the syntax-semantics interface (Bornkessel-Schlesewsky & Schlesewsky, 2008;Kuperberg, 2007). These results do not support the view that phrasal composition is reflected by the N400 (Neufeld et al, 2016), nor are our findings in line with MEG studies indicating that compositional processing occurs at around 400 msec in the vmPFC (e.g. , 2013.…”
Section: Effects Of Phrasal Meaning Composition: P600 Modulationssupporting
confidence: 73%
“…However, even on integration or hybrid accounts, the N400 reflects forms of top-down, context-sensitive unification of word meaning, and not bottom-up, syntaxdriven composition. The result of Neufeld et al (2016), because of the time course of the observed ERP, is not a clear-cut instance of an N400. In light of functional models and previous evidence, therefore, the link between the N400 and syntax-driven meaning composition is tenuous.…”
Section: Neural Correlates Of Phrasal Compositionmentioning
confidence: 90%
See 1 more Smart Citation
“…Since our red-boat studies were in a sense a mini-version of the popular sentence versus list paradigm, a LATL effect made sense and usefully showed both the timing of this activity-not obtainable from fMRI or PET-and that the LATL is engaged by just a single step of composition, as opposed to needing a full sentence as a stimulus. When simple composition is measured with EEG, combinatory effects are seen in time-windows similar to the LATL and vmPFC effects observed in MEG [4].…”
Section: Step 1: Identifying Possible Neural Correlates Of Compositionmentioning
confidence: 73%
“…Certainly, our work shows that some results previously published could be confounded with expectancybased processes. This has been addressed clearly for Neufeld et al (2016); however this issue is also present in other reports using visual , 2013c and auditory (Bemis & Pylkkänen, 2013a) stimuli. In these cases, the authors do not analyze or plot the April 30, 2020 activity elicited before second word onset, and they do not discuss the potential issues that their experimental design entails.…”
Section: April 30 2020mentioning
confidence: 59%